Wearing ihram for men using interactive 3D web approach / Zubaidah Ariff - Ariff, Zubaidah (2004)
The "Panduan Pemakaian Ihram" prototype system is developing through the combination of interactive 3D element where it uses three-dimensional character animation especially human animation and the web. The interest of developing this application is to bring a new dimension of approach in delivering the information for "Panduan Pemakaian Ihram". Normally in the day course, it needs somebody to be a model in showing how to wear "Ihram" but in this prototype system, no more human model will be necessary. Instead of that, the animation and simulation of 3 dimensional models is used. This report discusses the implementation and the findings of "Panduan Pemakaian Ihram" as a new approach in interactive multimedia. Systematic methods based on multimedia framework have been chosen to implement multimedia 3D relating to this system. In addition, a powerful computer system together with the appropriate 3D authoring tools is identified in order to fulfill this system prototype requirement. Questionnaires are used in the finding resuU of the development of 3D as a learning tool